2022
DOI: 10.3390/genes13061039
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Genomic Variants and Worldwide Epidemiology of Prostate Cancer

Abstract: Prostate cancer (PCa) incidence and mortality vary across territories and populations. This can be explained by the genetic factor of this disease. This article aims to correlate the epidemiological data, worldwide incidence, and mortality of PCa with single-nucleotide polymorphisms (SNPs) associated with the susceptibility and severity of this neoplasm in different populations. Eighty-four genetic variants associated with prostate cancer susceptibility were selected from the literature through genome associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Similar research has been done, where genes were extracted to correlate epidemiology of prostate cancer via each SNP genomic variant, where the genes would predict mortality or incidence [ 26 ]. The SNPS that overlapped were rs6983267 ( CCAT2 ), rs2066827 ( CDKN1B ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar research has been done, where genes were extracted to correlate epidemiology of prostate cancer via each SNP genomic variant, where the genes would predict mortality or incidence [ 26 ]. The SNPS that overlapped were rs6983267 ( CCAT2 ), rs2066827 ( CDKN1B ).…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms are located in genes such as HNF1B, CASC8, CDKN1B and others that are implicated in the regulation of cell cycle, metabolic pathways and cell division. These variants are more frequent in African population that show a greater risk of PCa compared with other ethnic groups (17).…”
Section: Susceptibility Polymorphismsmentioning
confidence: 95%
“…Therefore, subjects carrying the METH G-allele might have an increased PCa risk (15,16). Another study reported that different SNPs are correlated with PCa predisposition; in particular, the variants rs7000448, rs1048169, rs2961144, rs4430796, rs12500426, rs2066827 and rs114798100 seem to correlate with PCa incidence (17). These polymorphisms are located in genes such as HNF1B, CASC8, CDKN1B and others that are implicated in the regulation of cell cycle, metabolic pathways and cell division.…”
Section: Susceptibility Polymorphismsmentioning
confidence: 99%
“…Prostate cancer (PCa) is the second most prevalent malignancy and the fifth most common factor in cancer-related deaths, with a 13.5% incidence rate and a 6.7% mortality rate among men worldwide [ 1 , 2 ]. Prostatic tumours, both benign and malignant, are uncommon among men before the age of 40 and are more prevalent with age.…”
Section: Introductionmentioning
confidence: 99%